Successful interviewing : techniques for hiring, coaching, and performance management meetings - Arthur, Diane (American Management Association, 2000)
The skills needed to conduct all types of business interviews and ensure legal compliance. Here is the book that can turn non-interviewers into good interviewers-and good interviewers into great interviewers. Whether you're a general manager or human resources specialist, the fact is that you do some interviewing (formally or informally) virtually every day. This book will help you sharpen such skills as open-ended questioning, active listening, and reading body language-all essential in a variety of management situations. You'll learn to apply these techniques to 12 types of business intervie.